2010
DOI: 10.1152/ajprenal.00619.2009
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of kidneys during repair from AKI reveals possible roles for NGAL and KIM-1 as biomarkers of AKI-to-CKD transition

Abstract: Acute kidney injury (AKI) is being increasingly shown to be a risk factor for chronic kidney disease (CKD), but little is known about the possible mechanistic links. We hypothesized that analysis of the genomic signature in the repair stage after AKI would reveal pathways that could link AKI and CKD. Unilateral renal pedicle clamping for 45 min was performed in male C57BL/6J mice. Mice were euthanized at 3, 10, and 28 days after ischemia-reperfusion injury (IRI). Total RNA was isolated from kidney and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(149 citation statements)
references
References 44 publications
8
139
0
2
Order By: Relevance
“…These clinical findings are supported by preclinical data that mirror those risk factors identified in large observational studies (17,(32)(33)(34).…”
Section: Aki To Ckd In Adultssupporting
confidence: 61%
See 1 more Smart Citation
“…These clinical findings are supported by preclinical data that mirror those risk factors identified in large observational studies (17,(32)(33)(34).…”
Section: Aki To Ckd In Adultssupporting
confidence: 61%
“…The main mechanisms incriminated in CKD progression include inappropriate vascular, interstitial, and tubular regeneration after AKI (17). These maladaptive processes appear to be linked to impaired angiogenesis and reduced endothelial proliferation (35,36), cell cycle arrest (37), persistent fibrosis (38), epigenetic changes (33), increased expression in kidney tissue microRNAs associated with renal fibrosis (39), and ongoing inflammation (34). Further research to identify potential therapeutic targets to mitigate CKD progression after AKI in humans is urgently needed.…”
Section: Aki To Ckd In Adultsmentioning
confidence: 99%
“…Preliminary studies have reported on the potential utility of KIM-1 as a CKD biomarker (23,24). Animal models of AKI-to-CKD transition have identified NGAL and KIM-1 as two of the most upregulated genes and proteins in the kidney, revealing a possible role for these proteins as potential biomarkers to predict risk of CKD after AKI (25). The persistent elevation in KIM-1 and IL-18 in AKIpositive patients suggests ongoing kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several promising biomarkers have emerged from these studies (16,17). Analysis of temporal and spatial differences in their expression highlights the cellular complexity of the AKI response (ref.…”
Section: Introductionmentioning
confidence: 99%